The Transcription Factor StuA Regulates Central Carbon Metabolism,Mycotoxin Production, and Effector Gene Expression in the WheatPathogen Stagonospora nodorum - Ip-Cho, S.; Tan, Kar-Chun; Koh, G.; Oliver, Richard; Trengove, R.; Solomon, P. (American Society for Microbiology, 2010)
The Stagonospora nodorum StuA transcription factor gene SnStuA was identified by homology searching inthe genome of the wheat pathogen Stagonospora nodorum. Gene expression analysis revealed that SnStuAtranscript abundance increased throughout infection and in vitro growth to peak during sporulation. Toinvestigate its role, the gene was deleted by homologous recombination. The growth of the resulting mutantswas retarded on glucose compared to the wild-type growth, and the mutants also failed to sporulate. Glutamateas a sole carbon source restored the growth rate defect observed on glucose, although sporulation remainedimpaired. The SnstuA strains were essentially nonpathogenic, with only minor growth observed around thepoint of inoculation. The role of SnstuA was investigated using metabolomics, which revealed that this gene’sproduct played a key role in regulating central carbon metabolism, with glycolysis, the TCA cycle, and aminoacid synthesis all affected in the mutants. SnStuA was also found to positively regulate the synthesis of themycotoxin alternariol. Gene expression studies on the recently identified effectors in Stagonospora nodorumfound that SnStuA was a positive regulator of SnTox3 but was not required for the expression of ToxA. Thisstudy has uncovered a multitude of novel regulatory targets of SnStuA and has highlighted the critical role ofthis gene product in the pathogenicity of Stagonospora nodorum